Morphological and Functional Characterization of IL-12Rβ2 Chain on Intestinal Epithelial Cells: Implications for Local and Systemic Immunoregulation - Regoli, Mari; Man, Angela; Gicheva, Nadhezda; Dumont, Antonio; Ivory, Kamal; Pacini, Alessandra; Morucci, Gabriele; Branca, Jacopo J. V.; Lucattelli, Monica; Santosuosso, Ugo; Narbad, Arjan; Gulisano, Massimo; et al. (Frontiers in Immunology, 2018)
Interaction between intestinal epithelial cells (IECs) and the underlying immune systems is critical for maintaining intestinal immune homeostasis and mounting appropriate immune responses. We have previously showed that the T helper type 1 (TH1) cytokine IL-12 plays a key role in the delicate immunological balance in the gut and the lack of appropriate levels of IL-12 had important consequences for health and disease, particularly with regard to food allergy. Here we sought to understand the role of IL-12 in the regulation of lympho-epithelial cross talk and how this interaction affects immune responses locally and systemically. Using a combination of microscopy and flow cytometry techniques we observed that freshly isolated IECs expressed an incomplete, yet functional IL-12 receptor (IL-12R) formed solely by the IL-12R2 chain that albeit the lack of the complementary IL-121 chain responded to ex-vivo challenge with IL-12. Furthermore, the expression of IL-12R2 on IECs is strategically located at the interface between epithelial and immune cells of the lamina propria (lp) and using in vitro co-culture models and primary intestinal organoids we showed that immune-derived signals were required for the expression of IL-12R2 on IECs. The in vivo biological relevance of the IEC-associated IL-12R2 was assessed in vivo in a mouse model of food allergy characterized by allergy-associated diminished intestinal levels of IL-12 and in chimeric mice that lack the IL-12R2 chain on IECs. These experimental models enabled us to show that the anti-allergic properties of orally delivered recombinant Lactococcus lactis secreting bioactive IL-12 (rLc-IL12) were reduced in mice lacking the IL-122 chain on IECs. Finally, we observed that the oral delivery of IL-12 was accompanied by the down-regulation of the production of the IEC-derived pro-allergic cytokine thymic stromal lymphopoietin (TSLP). However, further analysis of intestinal levels of TSLP in IL-12R2-/- mice suggested that this event was not directly linked to the IEC-associated IL-12R2 chain. We interpreted these data as showing that IEC-associated IL12R2 is a component of the cytokine network operating at the interface between the intestinal epithelium and immune system that plays a role in immune regulation.